Structural and Optical Properties for Zn Doped CdO Thin Films Prepared by Pulse Laser deposition - Mustafa, Dhia Aldin Sleibi; Al-Rawi, Rawaa Isam Mohammed (Iraqi Journal of Science, 2018)
In this work, the effect of Zn dopant on structural and optical properties of cadmium oxides, CdO, thin film were studied prepared by pulse laser deposition on glass substrate then annealed at 250 ᵒC in air. All films were examined by X-ray diffraction and UV- visible spectrometer. The XRD analysis shows appearance of new phase identical with hexagonal ZnO additional with cubic phase at high Zn content, which effected on the optical properties. The optical energy gap increase from 2.45 eV to 2.70 eV with increasing Zn content from 0 to 40 %.